Photodegradation of ethylene/propylene/polar monomers, Co-, and terpolymers. II. prepared by Ni catalyst systems - Fernandes, Susete N.; Correia, Sandra; Matos, Ines; Marques, Maria M.; Rana, Sravendra; Kumar, Bijandra; Gupta, M. K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
The copolymers of ethylene/propylene as well as their terpolymers with polar monomers were prepared by Ni-catalyst systems and their photodegradation behavior was studied by Fourier transform infrared spectroscopy. The polar monomers used to synthesize co- and terpolymers of ethylene/propylene/polar monomer were 5-hexen-1-ol, 10-undecen-1-ol, acrylamide, methylmethacrylate, acrylonitrile, and methylvinyl ketone. The morphological changes of the irradiated samples were determined by scanning electron microscopy. The photodegradation kinetics has also been studied. The surface damage caused by polychromatic irradiation (lambda >= 290 nm) at 55 degrees C in atmospheric air is presented in different micrographs. The rate of photo-oxidative degradation is very fast in terpolymers containing polar monomers as compared with copolymers and homopolymers. The morphological study of the photodegraded samples showed a very good correlation with the photodegraded results. (c) 2007 Wiley Periodicals, Inc.
Keywords: copolymerization; Ethylene; Photodegradation; polar monomers; propylene

Preparation and characterization of novel hybrid of chitosan-g-PDMS and sodium montmorrilonite - Depan, Dilip; Kumar, Bijandra; Singh, Raj Pal (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2008)
Preparation and properties of Chitosan (CS)-clay nanocomposites grafted with polydimethyl siloxane (PDMS) with different clay ratios are herein discussed. CS is intercalated into sodium montmorrilonite and PDMS is grafted onto CS under UV irradiation. Sample films of CS intercalated into clay and grafted with PDMS were prepared by solvent casting method with varying amount of nanoclay and PDMS. They were characterized by conventional techniques such as X-ray diffractometry, fourier transform infrared spectroscopy, C-13 NMR, thermo gravimetric analysis, and differential thermal analysis. Sorption behavior of samples has been followed by measuring swelling degree and issues on the interactions of biopolymers with clay are also discussed. The water absorption of composites films reduces with an increase in the amount of incorporated clay. This is due to the barrier formation in the form of cross-linking points, which prevents water permeation into CS. The amount of adsorbed water is more, when the amount of CS exceeds the amount of PDMS. This shows high water retention capacity of CS. (c) 2007 Wiley Periodicals, Inc.
Keywords: Chitosan; graft copolymerization; Nanocomposites; PDMS; water absorption

Photodegradation of EPDM/MWCNT nanocomposites: effect of singlet oxygen - Kumar, Bijandra; Kumar, Indresh; Singh, R. P. (Polymer Composites, 2009)
The photo-oxidation of ethylene propylene diene monomer (EPDM)/multiwall carbon nanotubes (MWCNT) nanocomposites has been studied under accelerated UV-irradiation (lambda >= 290 nm) in the presence of singlet oxygen. The rate of photodegradation of EPDM/MWCNT is found to be higher when compared to the pristine polymer in presence of singlet oxygen. The enhancement of the rate of degradation of composite has been described through [2 + 2] photocycloaddition reaction between singlet oxygen and double bonds on composite which is followed by cleavage. The rate of degradation and the formation of new functional groups on the composite has been monitored by FTIR spectroscopy and found to be increased with irradiation time. The changes in surface morphology have been studied by scanning electron microscope. Differential scanning calorimetry measurements revealed an increase in the glass transition temperature of photodegraded EPDM and EPDM/MWCNT nanocomposites. POLYM. COMPOS., 30:855-860, 2009. (C) 2008 Society of Plastics Engineers

Vapour sensing with conductive polymer nanocomposites (CPC): polycarbonate-carbon nanotubes transducers with hierarchical structure processed by spray layer by layer - Lu, Jianbo; Kumar, Bijandra; Castro, Mickael; Feller, Jean-Francois (Sensors and Actuators B-Chemical, 2009)
The development of conductive polymer nanocomposite (CPC) sensors for volatile organic compounds (VOC) detection has been carried out using a spray layer by layer (LbL) process. This technique was successfully used to hierarchically structure polycarbonate-multiwall carbon nanotubes (PC-CNT) solutions into a double percolated architecture as attested by atomic force microscopy (AFM) and optical microscopy (OM). PC-CNT vapour sensing behaviour was investigated as a function of CNT content, films thickness, vapour flow and vapours solubility parameter. The response ranking A(r)(toluene)>A(r)(methanol)>A(r)(water)of PC-CNT was found to be coherent with kappa(12) Flory-Huggins interaction parameters provided that signals are normalised by analyte molecules number. Signals shape was interpreted to the light of Langmuir-Henry-Clustering (LHC) model and found to be proportional to vapour content. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Atomic force microscopy; carbon nanotube; Chemo-electrical behaviour; Conductive polymer nanocomposite; Vapour Sensing; Volatile organic compounds